Lean mass, muscle strength and gene expression in community dwelling older men: findings from the Hertfordshire Sarcopenia Study (HSS). - Patel, H; Al-Shanti, N; Davies, L; Barton, S; Grounds, MD; Tellam, R; Stewart, C; Cooper, C; Sayer, A (2014)
Sarcopenia is associated with adverse health outcomes. This study investigated whether skeletal muscle gene expression was associated with lean mass and grip strength in community-dwelling older men. Utilising a cross-sectional study design, lean muscle mass and grip strength were measured in 88 men aged 68-76 years. Expression profiles of 44 genes implicated in the cellular regulation of skeletal muscle were determined. Serum was analysed for circulating cytokines TNF (tumour necrosis factor), IL-6 (interleukin 6, IFNG (interferon gamma), IL1R1 (interleukin-1 receptor-1). Relationships between skeletal muscle gene expression, circulating cytokines, lean mass and grip strength were examined. Participant groups with higher and lower values of lean muscle mass (n = 18) and strength (n = 20) were used in the analysis of gene expression fold change. Expression of VDR (vitamin D receptor) [fold change (FC) 0.52, standard error for fold change (SE) ± 0.08, p = 0.01] and IFNG mRNA (FC 0.31; SE ± 0.19, p = 0.01) were lower in those with higher lean mass. Expression of IL-6 (FC 0.43; SE ± 0.13, p = 0.02), TNF (FC 0.52; SE ± 0.10, p = 0.02), IL1R1 (FC 0.63; SE ± 0.09, p = 0.04) and MSTN (myostatin) (FC 0.64; SE ± 0.11, p = 0.04) were lower in those with higher grip strength. No other significant changes were observed. Significant negative correlations between serum IL-6 (R = -0.29, p = 0.005), TNF (R = -0.24, p = 0.017) and grip strength were demonstrated. This novel skeletal muscle gene expression study carried out within a well-characterized epidemiological birth cohort has demonstrated that lower expression of VDR and IFNG is associated with higher lean mass, and lower expression of IL-6, TNF, IL1R1 and myostatin is associated with higher grip strength. These findings are consistent with a role of proinflammatory factors in mediating lower muscle strength in community-dwelling older men.